Contextual-Based Interactive Learning Video Media to Improve Science Learning Outcomes of Grade VI Elementary School Students - Ni Made Galuh Sariwedani; Basilius Redan Werang; I Komang Sudarma (Universitas Pendidikan Ganesha, 2025)
In the process of learning science in elementary schools, teachers often have difficulty in delivering learning materials due to the lack of availability of supporting learning media. As a result, during the learning process, students become bored, unfocused, and do not understand the contents of the material. This has an impact on student learning outcomes that are not optimal. The purpose of this study is to create interactive video learning media based on contextual science subjects that are valid and practical. The type of research used is development research with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The methods used to collect data are observation, interviews, documentation, questionnaires, and tests. The research instrument is a questionnaire. The data analysis technique is quantitative descriptive analysis. The results of this study indicate that the feasibility test of media and material experts obtained very feasible criteria with an average value of 95%. The results of the teacher's practicality test obtained a score of 99.09% with a very practical qualification. The results of this study obtained a tcount of 15.169 with a significance level of 5% is 1.703, so that tcount> ttable. Based on the research that has been conducted, it is concluded that there is a significant influence of Contextual-Based Interactive Learning Video Media on the science learning outcomes of grade VI Elementary School students.